Development of a methodology to estimate energy expenditure for various speeds of walking - Lima, Dartel Ferrari de (2002)
This work presents a methodology developed to obtain estimative equations relating the energy consume in several speeds of walking, relating the oxygen consume of young adult men, apparently healthy, the average corporal weight and walking in several speeds. The results showed that for distance unity, the lowest speeds isn’t necessarily the most thrifty. In time unity, as higher the speed, the expenditure of energy will be higher. The methodology used can be useful to obtain equations suitable for groups with different profiles, allowing comparative future works.